Lower Urinary Tract Symptoms in Uterine Myoma: A Systematic Review and Meta-Analysis - Lek-Hong Tan; Li-Hsien Tsai (Medicina)
Background and Objectives: Lower urinary tract symptoms (LUTSs) are prevalent among patients with uterine myoma (UM); however, these health issues have not been systematically evaluated. To address this research gap, this systematic review and meta-analysis synthesizes existing findings on the prevalence estimates and odds ratios for LUTSs in patients with UM. Materials and Methods: A systematic literature search using PubMed and Embase was conducted for articles published between 1 January 2000 and 24 September 2023. The search and review processes followed the PRISMA and MOOSE guidelines. This study was registered in PROSPERO (CRD42023474156). Data on the prevalence and odds ratios of LUTSs—including storage symptoms (frequency, urgency, nocturia), voiding symptoms, and urinary incontinence (UI) subtypes such as stress incontinence (SUI), urgency urinary incontinence (UUI), and mixed urinary incontinence (MUI)—were extracted. Pooled prevalence estimates and odds ratios were calculated using random-effects meta-analysis. Subgroup analyses and univariate meta-regression were conducted to examine associations with age, BMI, parity, WHO region, and risk of bias. The impact of UM size was assessed using standardized mean differences. Results: Of the 572 articles screened, 20 met the inclusion criteria. The overall pooled prevalence of LUTSs in UM patients was 49% (95% CI, 26–72%), with substantial heterogeneity across studies (I2 = 99.8%). The pooled prevalence for urinary frequency, urgency, nocturia, voiding dysfunction, and overall UI, SUI, UUI, and MUI ranged from 15% to 54%. SUI and UUI were significantly associated with UM (OR = 2.0, 95% CI: 1.2–3.3; OR = 1.5, 95% CI: 1.1–2.0, respectively). Hysterectomy was not associated with an improvement in overactive bladder (OAB) symptoms (OR = 1.9, 95% CI: 0.6–5.7). A larger UM size was not linked to worsening LUTS. Fourteen studies (70%) had some concerns about the risk of bias, while six studies (30%) had a low risk of bias. Egger’s test showed no significant publication bias (p = 0.19). Conclusions: Approximately half of patients with UM experience LUTSs or UI. The findings emphasize the need to consider urinary symptoms in UM management. Further research is warranted to reduce heterogeneity and explore treatment-specific outcomes.